Pengembangan Sistem Monitoring Penyandang Masalah Kesejahteraan Sosial Berbasis Web (Studi Kasus: Dinas Sosial Kota Malang) - Choirul Ichsan Basuki; Achmad Arwan; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
People with Social Welfare Problems (PMKS) are individuals, groups, and/or communities who due to an obstacle, difficulty, or disturbance, cannot carry out their social functions, so that their physical, spiritual, and social life needs cannot be fulfilled adequately and reasonably. In Malang, PMKS are handled by social service of Malang. Social service of Malang conducting raids to capture the PMKS and later placed into assessment camp. In assessment camp, social workers collect data on personal and health information from PMKS. PMKS is treated for several days or even weeks depending on physical and mental condition. In their handling, social service of Malang find several problems such as the data collection process and monitoring PMKS that were still done manually so the file was easily lost and difficult to recapitulate. Therefore, a web-based monitoring system was created to collect PMKS data and monitoring at the assessment camp. The development of the system uses the waterfall method because the requirements defined are clear. This research produces four actors, 47 functional requirements, and one non-functional requirement. The software testing uses some strategies, such a unit testing, integration testing, validation testing with 100% valid results. The results of compatibility testing indicate that the system runs in specified browser and device.